Praktik Murabahah Hewan Qurban pada Koperasi Syariah Al Abrar Surabaya dalam Perspektif Ekonomi Islam - Putri, Mayangsari Yuhana; A'rasy Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2022)
Al Abrar Sharia Cooperative has murabahah products for qurban animals with the aim of facilitating members or customers who wish to carry out qurban worship. However, in practice the sharia cooperative does not mention the amount of profit to customers, the profit is explained at the cooperative's annual meeting. This study aims to determine the practice of murabahah sacrificial animals at the sharia cooperative Al Abrar Surabaya in an Islamic economic perspective, whether the practice is in accordance with Islamic provisions, namely MUI DSN Fatwa No. 04 of 2000 concerning murabahah. The type of research is descriptive qualitative by analyzing the data obtained from the informants, triangulating the sources then giving an understanding and explanation about the practice of the murabahah contract of sacrificial animals. The research data was taken through primary data, namely the results of interviews with informants, namely cooperative leaders, customers, and MUI administrators. Secondary data were obtained from journals, books, articles and news related to the research. The results showed that the practice of murabahah sacrificial animals carried out by the Al Abrar Sharia Cooperative violated the general provisions in the sixth and seventh points so that it was not fully in accordance with the provisions of the MUI DSN Fatwa No. 04 of 2000.